Direct vinylogous oxidative cross-dehydrogenative coupling of 4-nitroisoxazoles with N-aryl tetrahydroisoquinolines in water under air conditions. Issue 3 (4th January 2017) - Zhang, Yong; Wei, Biao-Wen; Wang, Wen-Xin; Deng, Lei-Ling; Nie, Long-Jun; Luo, Hai-Qing; Fan, Xiao-Lin
Abstract : Using water as the solvent and air as the oxidant, a direct catalytic vinylogous cross-dehydrogenative coupling reaction was developed. Abstract : A direct vinylogous cross-dehydrogenative coupling (CDC) reaction of N -aryl tetrahydroisoquinolines with 3, 5-dialkyl-4-nitroisoxazoles catalysed by CuBr using air as the oxidant in water has been developed. This new strategy provides an efficient and environmentally benign way to access medicinally important isoxazole substituted tetrahydroisoquinoline derivatives under mild conditions.